OLYMPIC EDUCATION AND PHYSICAL EDUCATION: CREATIVE POTENTIAL OF INTERPLAY - Вржесневський, Іван Іванович; Янішевський, Юрій Володимирович (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
Along with the positive trends in the development of modern post-industrial society, scientists also observe the negative signals and prerequisites for the future prospects of mankind. In the pedagogical space, these prerequisites are resolved in the short-term orientation to the short-term interests and wishes of the student, the support of the pattern of "rational" person and the replacement of ideals for values ​​in the formation of the outlook of the young man. According to the authors, the modern education system is more oriented towards the creation of a personality that must function optimally in the consumption society and at the same time satisfy the wishes of clients (as an area of educational services). Therefore, the vital aspects of biological development and the advancement of the younger generations are viewed more in the context of their own choice of student or student, and in the socio-anthropological plane the prerogative of health care professionals. According to the authors, to correct the marked defects, it makes sense to reproduce in the pedagogy the ideals of comprehensive harmonious development, which should become in the context of the "physicality" of man a basic evolutionary strategy. Olympic education not only represents information, historical materials and references to the achievements of prominent sports figures in society, but also appeals to the time-tested ideals of Olympism, including human development. Physical education, as an anthropological constant of pedagogical constructs in society, requires not only short-term, tactical guidelines. In today’s society of excessive consumption and universal values, the young man lacks ideals related to virtues that accumulate moral, ethical and volitional aspects of education with the impulse to improve the biological nature of man and self-improvement. Therefore, the purpose of the article is to determine the potential of the interconnection and interplay of Olympic education and physical education of students. The study is devoted to the analysis of the interrelation of the basic factors of the ancient Olympic tradition and modern ideas about the use of the potential of Olympic education in the system of physical education of student youth. The specificity of the study involves the use of philosophical, anthropological, systemic, sociocultural approaches in the context of interdisciplinary research. The polemical questions of complex subtexts concerning the ideals and values of Olympism in modern pedagogical constructs are considered. The study violated the pedagogical, philosophical, anthropological and social prerequisites for defining the broadcasting of the ideas of Olympism in the contexts of both systemic and selective approaches. The material of theoretical generalizations reveals the nature of the pedagogical effects of "Olympic education". The potential of the symbiosis of Olympic education and physical education in the context of relaying the ideals of comprehensive harmonious human development has been revealed